Long‐term outcomes and risks factors for failure of intradetrusor onabotulinumtoxin A injections for the treatment of refractory neurogenic detrusor overactivity. Issue 2 (26th July 2017) - Joussain, Charles; Popoff, Mélanie; Phé, Véronique; Even, Alexia; Bosset, Pierre‐Olivier; Pottier, Sandra; Falcou, Laetitia; Levy, Jonathan; Vaugier, Isabelle; Chartier Kastler, Emmanuel; Schurch, Brigitte; Denys, Pierre
Abstract : Aims: Aims of this study were to assess the long‐term outcomes of Intradetrusor injection of OnabotulinumtoxinA (Botox® injection) associated with clean intermittent‐catheterization (CIC) for the treatment of neurogenic detrusor overactivity (NDO) and to identify risk factors for failure. Methods: Neurological patients with NDO using CIC who had received Botox® injections between January 2001 and September 2013 were included. Clinical, urodynamic and radiological data were recorded. Primary endpoint was failure and withdrawal rates after 3, 5, and 7 years of management. Survival curves of withdrawals and failures of treatment were calculated with a 95‐confidence interval using the Kaplan‐Meier method. Risk factors for failure were determined with univariate analysis and multivariate analysis using Cox model. Results: Overall, 292 patients, mean age of 40 ± 13, 6 years, were included. Overall, 219 patients (80.6%; IC95% [76.3‐85.4%]) were still treated with Botox® injections after 3 years, 128 (71.1%; IC95% [65.7%, 76.9%]) after 5 years, and 58 (60.8%, IC95% [54.0%, 68.4%]) after 7 years. Failure rate was 12.6% (IC95% [8.6‐16.5%]) after 3 years, 22.2% (IC95% [16.6‐27.3%]) after 5 years, and 28.9% (IC95% [21.9%; 35.3%]) after 7 years of follow‐up. Withdrawal rate after 7 years of follow‐up was 11.3% ( n  = 33/292). Severe NDO at baseline appears to be a significant risk factor for failure. Conclusion: This study confirms long‐term efficacy and tolerance of Botox® injection in patients with NDO using CIC. Long‐term failure and withdrawal rates remain low but significant, and need to be managed.